Gurdjieff Theologos. Issue 2 (1st February 2022) - Azize, Joseph
Abstract : G. I. Gurdjieff (1877[?]–1949) left a system of integrated ideas and practices which can provide promising fresh perspectives on stubborn theological conundrums, including teachings on God and the devil, angelic orders, creation, the soul, life-after-death, reincarnation and recurrence, free-will and determinism, the proper order of human life, and divine justice. Here I focus on Gurdjieff's ideas on suffering. Radically reframing the standard position, for Gurdjieff, God is not omnipotent, rather, the meaning of human life found in the possibility of helping God in the maintenance of the universe by transforming suffering. Thus, independently of the will of God, suffering is ineluctable; hence God and humanity are involved in the struggle with it. I then consider the practical aspects of his ideas on suffering: suffering providentially demands a response; a conscious response then transforms suffering, to the benefit of the sufferer and of the Creation.